2014
DOI: 10.4236/health.2014.61016
|View full text |Cite
|
Sign up to set email alerts
|

First normative reference of standing long jump indicates gender difference in lower muscular strength of Macedonian school children

Abstract: Background: This is the first study to publish the normative reference values for assessment of the level of muscular strength through the "standing long jump" test carried out on a large sample of Macedonian school children. The normative values encompass a wide span of years (6 -18). Methods: The research was realized in a large sample of 12618 school children at the age of 6 to 18 years from Macedonia. The sample was divided in 14 groups, according to chronological age and each age group was divided into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
4
10
0
Order By: Relevance
“…and in the Portuguese population 98.0 cm 45 . This tendency is also observed when comparing own results with the results from Macedonia 47 and Southern Spain 48 . Correlating the presented parentel values in terms of power to the European data 49 a higher level of strength (standing long jump) of Polish girls and preschool boys is also found.…”
Section: Discussionsupporting
confidence: 77%
“…and in the Portuguese population 98.0 cm 45 . This tendency is also observed when comparing own results with the results from Macedonia 47 and Southern Spain 48 . Correlating the presented parentel values in terms of power to the European data 49 a higher level of strength (standing long jump) of Polish girls and preschool boys is also found.…”
Section: Discussionsupporting
confidence: 77%
“…It was found from the study of Paul (2013), the average standing broad jump of 14 year old male students of 24 Pgs (N), West Bengal was 171.37 cm with S.D of 15.92. and for Macedonian school children it was 180.5 cm with S.D of 28.07 (Gontarev et al, 2014). Analysing the result of standing broad jump it may be concluded that the present study has close proximity to Paul (2013).…”
Section: Resultssupporting
confidence: 55%
“…The joints of the feet are measured by recording images and analyzing by sitting straight with the knees touching the floor and doing maximum flexion of the tapered leg (point) and extension of the knee leg in the same way. Measuring leg power using a standing long jump is a measurement instrument that can see the power criteria for a certain age [18]. Judging of the Split Leap Movement (with criteria by nationally licensed Jury) with the criteria according to motion as discrete motion.…”
Section: Methodsmentioning
confidence: 99%